Diagnostic Detection of Allelic Losses and Imbalances by Next-Generation Sequencing - Dubbink, Hendrikus J.; Atmodimedjo, Peggy N.; van Marion, Ronald; Krol, Niels M.G.; Riegman, Peter H.J.; Kros, Johan M.; van den Bent, Martin J.; Dinjens, Winand N.M. (The Journal of molecular diagnostics : JMD, 2016)
Cancer cells are genomically unstable and accumulate tumor type–specific molecular aberrations, which may represent hallmarks for predicting prognosis and targets for therapy. Co-deletion of chromosomes 1p and 19q marks gliomas with an oligodendroglioma component and predicts a better prognosis and response to chemotherapy. In the current study, we present a novel method to detect chromosome 1p/19q co-deletion or loss of heterozygosity (LOH) in a diagnostic setting, based on single-nucleotide polymorphism (SNP) analysis and next-generation sequencing (NGS). We selected highly polymorphic SNPs distributed evenly over both chromosome arms. To experimentally determine the sensitivity and specificity of targeted SNP analysis, we used DNAs extracted from 49 routine formalin-fixed, paraffin-embedded glioma tissues and compared the outcome with diagnostic microsatellite-based LOH analysis and calculated estimates. We show that targeted SNP analysis by NGS allows reliable detection of 1p and/or 19q deletion in a background of 70% of normal cells according to calculated outcomes, is more sensitive than microsatellite-based LOH analysis, and requires much less DNA. This specific and sensitive SNP assay is broadly applicable for simultaneous allelic imbalance analysis of multiple genomic regions and can be incorporated easily into NGS mutation analyses. The combined mutation and chromosomal imbalance analysis in a single NGS assay is suited perfectly for routine glioma diagnostics and other diagnostic molecular pathology applications.